Comparing the efficacy of therapeutic Thai acupressure on plantar acupoints and laser cane therapy on freezing of gait in Parkinson’s disease: a randomized non-inferiority trial - Miyahara, Yuka; Phokaewvarangkul, Onanong; Kerr, Stephen; Anan, Chanawat; Toriumi, Haruki; Bhidayasiri, Roongroj (Frontiers in Neurology, 2024)
Background ON-freezing of gait (ON-FOG) in Parkinson’s disease (PD), often resistant to medication, is linked to sensory deficits and proprioceptive impairment, and results in falls and reduced life quality. While visual cues from a laser cane (LC), which rapidly accesses the motor cortex, are commonly used to compensate for proprioceptive impairment, increased visual reliance may be affected by disease progression. Emerging evidence suggests that modulation of peripheral sensory processing may alleviate ON-FOG, and therapeutic Thai acupressure (TTA) may be a solution. This study aims to evaluate the effect of TTA in alleviating ON-FOG and compare its effectiveness to LC in patients with PD. Methods This open-label, non-inferiority trial randomized 90 PD patients with ON-FOG equally into three arms: TTA for plantar nerve stimulation for 96 s, LC for visual cueing, and sham control (SC). Stride length was the primary non-inferiority endpoint [non-inferiority margin: lower limit of 95% confidence interval (CI) above −10 cm in mean change difference in pre- and immediately post-intervention in TTA versus LC (one-sided)]. Secondary outcomes included FOG episodes, double support time, velocity, cadence, step length, timed up and go (TUG) test, and visual analog scale (VAS) score. Results TTA showed non-inferiority to LC in stride length (mean = −0.7 cm; 95% CI: −6.55; 5.15) (one-sided). The improvements with TTA and LC versus SC were comparable between (mean = 13.11 cm; 95% CI: 7.26; 18.96) and (mean = 13.8 cm; 95% CI: 7.96; 19.65) (one-sided). Secondary outcomes favored TTA and LC over SC with improved FOG, velocity, step length, and VAS scores, while only TTA resulted in improved double support time, cadence, and TUG test results. No complications occurred. Conclusion The efficacy of TTA, which improves stride length, is non-inferior to that of LC and consequently alleviates FOG comparable to LC. TTA might enhance proprioceptive function and reduce visual dependence. Therefore, TTA, characterized by its non-invasive, simple, and safe techniques, is a potential non-pharmacological alternative for ON-FOG treatment and might enhance overall quality of life. However, further research into the mechanism, efficacy, and utilization of TTA is essential. Clinical trial registration https://www.thaiclinicaltrials.org/show/TCTR20200317001, identifier TCTR20200317001.